Effect of the bs 1 gene in plantainbanana hybrids on response to black sigatoka - Craenen, K.; Ortíz, R. (Springer, 1997)
Use of resistant host genotypes is an important component of an integrated approach to control black sigatoka, a disease caused by the fungus Mycosphaerella fijiensis Morelet. The objective of the present research was to determine the role of the major gene for black sigatoka resistance (bs1) in the host response to this disease. Euploid hybrids with a known genotype for the bs1 locus were derived from triploid-diploid crosses of two French plantains and a diploid wild banana, and were assessed for their host response to black sigatoka in plant and ratoon crops in the humid forest zone of Nigeria. Host response was determined at flowering by recording the number of standing leaves, the youngest leaf with symptoms, the youngest leaf spotted, the total leaf area attacked by black sigatoka, and an index of the leaves spotted. An analysis of frequency distribution in each segregating population showed that almost all the traits displayed a normal distribution across ploidy level. This suggests that additive gene action plays an important role in the host-plant response to the fungus. Heritability, repeatibility, and intraclass correlations were calculated. The environment and the genotype-by-environment interaction significantly affected the host response to black sigatoka, which explains the low repeatibility of all traits. The intrafamily variation was larger than the interfamily variation, and most of the genetic variation in each family depended on the individual genotypes, regardless of their ploidy. The additive effect of, and the intralocus interaction at, the bs1 locus on host response to black sigatoka were established by a one-way analysis of variance and regression analyses. Intralocus interaction in the bs1 locus apparently regulates the appearance of symptoms on the leaf surface, whereas the additive effect and the intralocus interaction of the bs1 locus affect disease development in the host plant. Therefore, the gene action(s) at the bs1 locus may provide durable resistance to black sigatoka by slowing down disease development in the host plant.